A thermally robust and optically transparent infrared selective emitter for compatible camouflage. Issue 42 (7th October 2021) - Zhang, Lei; Wang, Jun; Lou, Jing; Zhu, Ying; Gui, Boheng; Feng, Mingde; Wang, Jiafu; Qu, Shaobo
Abstract : The proposed ITO/ZnS/ITO/ZnS composite film is simple in geometry, functional in use, but complex in mechanism, which may promote its pratical application in infrared-visible compatible camouflage. Abstract : Infrared selective emitters (ISEs) are capturing growing attention of researchers due to their specific functionality of tuning infrared radiance to camouflage objects into the background, which provides efficient access to improved infrared camouflage performance (CP). However, general ISEs with in-plane structures are not suitable for fabrication on a large scale or compatible with the visible band. In this study, thermally robust and optically transparent ISEs based on ITO/ZnS four-layer composite films are proposed and verified experimentally. The lossy layer of semi-transmissive ITO film and top layer of anti-reflective ZnS film are found to be primarily responsible for tuning the performance of selective emission. For the first time, an ISE exhibiting superior selective emission properties in dual undetected bands of 2.5–3 μm and 5–8 μm is proposed, which simultaneously possesses high transmittance in the visible band. Moreover, these infrared-visible properties of the composite films are thermally stable and robust from room temperature to 700 K, presenting suitability for scalable manufacturing and long-time service. This work would greatly improve the engineered application of selective emitters with large-scale fabrication in infrared-visible compatible camouflage.